Analisis Kehilangan Hasil Pada Rantai Pasok Komoditas Pakcoy (Brassica rapa L.) - Rahmani, Alya; Perdana, Tomy; Setiawati, Fitri Sulis (Universitas Galuh, 2024)
Food loss of pakcoy commodity at each stage of the supply chain causes losses to the company. The purpose of this study is to calculate the percentage, identify the causes of food loss and strategies that can be done to reduce food loss in the pakcoy commodity supply chain at CV. Bumi Agro Technology. The research was conducted at CV. Bumi Agro Technology located at Jl. Baruajak, West Bandung Regency, Lembang, West Java and PT A which is a partner of the company. The method used used a qualitative design with a case study approach. Data was obtained through observation and interviews. This research uses Pareto Diagram analysis, Root Cause Analysis (RCA), and Causal Loop Diagram (CLD). The results showed that the loss of the pakcoy commodity supply chain at PT A reached 32.6% which affected the income of CV. Bumi Agro Technology with a loss of Rp3,996,000. The main causes of food loss are Natural Resources (SDA) and Plant Disturbing Organisms (OPT). Strategies to reduce food loss using preventive methods with a circular economy principle approach, namely by collecting and processing agricultural waste into organic fertiliser and using protected agriculture.